What are the ‘active ingredients’ of interventions targeting the public's engagement with antimicrobial resistance and how might they work? - McParland, Joanna L.; Williams, Lynn; Gozdzielewska, Lucyna; Young, Mairi; Smith, Fraser; MacDonald, Jennifer; Langdridge, Darren; Davis, Mark; Price, Lesley; Flowers, Paul (British journal of health psychology, 2018)
Objectives Changing public awareness of antimicrobial resistance (AMR) represents a global public health priority. A systematic review of interventions that targeted public AMR awareness and associated behaviour was previously conducted. Here, we focus on identifying the active content of these interventions and explore potential mechanisms of action. Methods The project took a novel approach to intervention mapping utilizing the following steps: (1) an exploration of explicit and tacit theory and theoretical constructs within the interventions using the Theoretical Domains Framework (TDFv2), (2) retrospective coding of behaviour change techniques (BCTs) using the BCT Taxonomy v1, and (3) an investigation of coherent links between the TDF domains and BCTs across the interventions. Results Of 20 studies included, only four reported an explicit theoretical basis to their intervention. However, TDF analysis revealed that nine of the 14 TDF domains were utilized, most commonly ‘Knowledge’ and ‘Environmental context and resources’. The BCT analysis showed that all interventions contained at least one BCT, and 14 of 93 (15%) BCTs were coded, most commonly ‘Information about health consequences’, ‘Credible source’, and ‘Instruction on how to perform the behaviour’. Conclusions We identified nine relevant TDF domains and 14 BCTs used in these interventions. Only 15% of BCTs have been applied in AMR interventions thus providing a clear opportunity for the development of novel interventions in this context. This methodological approach provides a useful way of retrospectively mapping theoretical constructs and BCTs when reviewing studies that provide limited information on theory and intervention content. Statement of contribution What is already known on this subject? Evidence of the effectiveness of interventions that target the public to engage them with AMR is mixed; the public continue to show poor knowledge and misperceptions of AMR. Little is known about the common, active ingredients of AMR interventions targeting the public and information on explicit theoretical content is sparse. Information on the components of AMR public health interventions is urgently needed to enable the design of effective interventions to engage the public with AMR stewardship behaviour. What does this study add? The analysis shows very few studies reported any explicit theoretical basis to the interventions they described. Many interventions share common components, including core mechanisms of action and behaviour change techniques. The analysis suggests components of future interventions to engage the public with AMR.